Research on Unsteady Wake Characteristics of the NREL 5MW Wind Turbine Under Yaw Conditions Based on a LBM-LES Method - Xue, Feifei; Xu, Chang; Huang, Haiqin; Shen, Wenzhong; Han, Xingxing; Jiao, Zhixiong (Frontiers in Energy Research, 2022)
The yaw of a large-scale wind turbine will change the aerodynamic performance of its substructures. In view of this, this article applied a LBM-LES method to numerically simulate the yawed MEXICO wind turbine and compared the numerical results with the experimental data collected in the New MEXICO experiment to verify the reliability of the method. A rapid dynamic yaw is defined with a yaw speed of 5°/s in yaw control, while a slow dynamic yaw is with a yaw speed of 0.3°/s. The NREL 5 MW offshore wind turbine was used to explore the constant wake characteristics under the conditions of a rapid dynamic yaw and of a slow dynamic yaw. It can be seen from the results that the LBM-LES method captures the detailed characteristics of the complex unsteady flow field of the wind turbine. In the rapid dynamic yaw process, the transition area between the far wake and the near wake shows a large deflection. However, in the process of the slow dynamic yaw, the far wake deflects forward relatively to the yaw. The dynamic yaw wake forms a kidney-shaped cross-section similar to the one in a steady yaw. The yaw wake recovers faster than the wake without yaw, and the rapid dynamic yaw wake has an asymmetric structure. The thrust of the wind turbine drops rapidly during the rapid dynamic yaw, while the thrust of the slow dynamic yaw decreases gradually. The thrust drops three times per rotor revolution, and the time of thrust decrease is delayed as the yaw angle increases.